DEVELOPING PRAGMATIC COMPETENCE IN FOREIGN LANGUAGE CLASSROOMS: METHODS AND PEDAGOGICAL IMPLICATIONS - Rustamova Feruzabonu Ilkhomovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: Pragmatic competence has become a central component of communicative language teaching, reflecting learners’ ability to use language appropriately in social contexts. This article explores effective methods for developing pragmatic competence in foreign language classrooms, emphasizing the integration of sociocultural, discourse, and functional aspects of language use. Drawing on contemporary linguistic and pedagogical theories, the study discusses instructional strategies such as role-play, authentic materials, task-based learning, and digital interaction. The paper argues that explicit and implicit teaching approaches must be combined to achieve optimal outcomes. Ultimately, enhancing pragmatic competence contributes significantly to learners’ communicative effectiveness and intercultural awareness in globalized educational environments.